(untitled) (American Journal of Management, 2022)
Strategic IT alignment is seen in “an overwhelming body of literature” (Sabherwal, Sabherwal, Havakhor, & Steelman, 2019, p. 454) as the state of congruence between an organization’s IT strategy and the organizations business strategies. Strategy is the plan for getting from where you or your organization is to where it wants to be (Webb, 2019). Generally, organization management has the task of coming up with the strategy and the workers have the task of implementing that strategy. These two groups should agree on the current situation, what the strategy is, how to implement it, and the ultimate goals. When the two groups do not agree, implementing the strategy is difficult at best and impossible at worst. This paper explores how the mental models (Johnson-Laird, 2010) an organization’s strategy of IT personnel transition in the minds of management (Chief Information Officers) and workers (analysts). Revealed causal mapping brings these mental models to light so they can be compared, and where the mental models differ, action can be taken so management and workers are all on the same page.